Complex therapy of musculoskeletal pain: the role of centrally acting muscle relaxants - A. E. Karateev; L. I. Alekseeva; I. F. Akhtyamov; L. M. Antonenko; F. I. Devlikamova; I. S. Dydykina; S. A. Zhivolupov; A. V. Kuzin; V. A. Parfenov; I. N. Samartsev; M. M Tanashyan; N. V. Titova (Современная ревматология, 2024)
Chronic pain is the main manifestation of musculoskeletal diseases (MSDs), leading to deterioration of quality of life and loss of ability to work. The importance of this problem is determined by the widespread prevalence of MSDs, osteoarthritis (OA), acute and chronic non-specific back pain (NBP), periarticular soft tissues lesions. Introduction of effective methods of treatment of musculoskeletal pain (MSP) into medical practice is one of the fundamental tasks of modern medicine.The pathogenesis of MSP includes mechanisms such as injury, inflammation, peripheral sensitization, biomechanical disorders, dysfunction of the nociceptive system and psychoemotional disorders. Painful muscle tension plays an important role in the development of MSP, especially in NBP. Given the complex pathogenesis of MSP, its treatment is based on the combined use of drugs with different mechanisms of action and nonpharmacological methods. Non-steroidal anti-inflammatory drugs (NSAIDs) have a central place in this context. However, they can cause serious adverse reactions (ARs), so when choosing NSAIDs, it is necessary to consider comorbid pathology and risk factors. One of the most acceptable NSAIDs with a pronounced analgesic effect and low incidence of ARs is aceclofenac, which is available in various dosage forms (tablets, sachets, topical cream for external use). This medication is characterized by proven efficacy and good tolerability.Centrally acting muscle relaxants (CM) play an important role in the treatment of MSP. They eliminate muscle spasm, enhance the effect of analgesics and reduce the need for NSAIDs. The effect of CM has been demonstrated in spasticity and NBP. However, the use of many drugs of this group can be associated with serious ARs, which limits their use.Tolperisone has the best combination of efficacy and favorable safety profile among CM. Its positive effect in the complex treatment of NBP has been confirmed in several well-organized, placebo-controlled trials. There are also studies demonstrating the efficacy of tolperisone in OA. An important advantage of this drug is virtually no sedative effect, and no negative impact on hemodynamics and on the ability to perform concentration-intensive work. Emergence of a new form of tolperisone – extended-release tablets (Mydocalm® Long 450 mg) – increases patient compliance with CM therapy and facilitates the physician's work.